2016
DOI: 10.18632/oncotarget.11424
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms incorporated serum direct bilirubin level for predicting prognosis in stages II and III colorectal cancer after radical resection

Abstract: An elevated serum bilirubin has been reported to be associated with a reduced risk of some cancer; however, the prognostic significance of serum bilirubin in colorectal cancer wasn’t fully understood. The purpose of this study was to evaluate whether serum bilirubin could predict the prognosis of patients in stages II and III colorectal cancer. A retrospective cohort of 986 patients with colorectal cancer who received surgical resection between January 2005 and December 2010 was included in the study. Levels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…D, Kaplan-Meier curves of OS in patients with H-DBIL or L-DBIL as well as with or without lymph-node metastasisAmong the different types of bilirubin, we noticed that although TBIL and IBIL were significantly decreased in patients with OSCC, only DBIL predicted overall survival. This is consistent with Zhang's results,14 which demonstrated that pre-treatment serum DBIL, but not TBIL or IBIL, was an independent prognostic factor for both overall survival (OS) and disease-free survival (DFS) in stage II and stage III colorectal cancer (CRC) patients. A high DBIL level correlated with lymph-node metastases and lymphovascular invasion.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…D, Kaplan-Meier curves of OS in patients with H-DBIL or L-DBIL as well as with or without lymph-node metastasisAmong the different types of bilirubin, we noticed that although TBIL and IBIL were significantly decreased in patients with OSCC, only DBIL predicted overall survival. This is consistent with Zhang's results,14 which demonstrated that pre-treatment serum DBIL, but not TBIL or IBIL, was an independent prognostic factor for both overall survival (OS) and disease-free survival (DFS) in stage II and stage III colorectal cancer (CRC) patients. A high DBIL level correlated with lymph-node metastases and lymphovascular invasion.…”
supporting
confidence: 91%
“…For example, Gao et al used a cutoff value of 2.6 μmol/L to predict prognosis in Chinese rectal cancer patients, and Li et al adopted 3.45 μmol/L for NSCLC . In a study of colorectal cancer, Zhang et al used 3.6 μmol/L to categorize lower or higher DBIL levels . The incidence of lung cancer or colorectal cancer is higher than OSCC, and the living habits of patients with different cancers vary; therefore, the cutoff value may also vary between studies using different samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that non-small cell lung cell cancer patients with higher pretreatment bilirubin levels had longer OS, DFS, and DMFS than those with lower levels [8]. Zhang and colleagues also found that high DBIL was strongly associated with worse outcomes after surgery in colorectal cancer patients with stage II and stage III disease in a retrospective study [9]; subsequent studies confirmed these results [13, 14]. However, the association between serum bilirubin levels and clinical outcomes in gastric cancer had not been examined.…”
Section: Discussionmentioning
confidence: 99%